HistoriAR: Experience Indonesian history through interactive game and augmented reality - Shintia Trista; Andre Rusli (Institute of Advanced Engineering and Science, 2020)
History has a vital function in shaping the personality of the nation, the quality of humans, and the people of a country. However, one factor that influences learning behavior that could be improved is the students’ interest in learning. The use of game-based learning has been proven to be effective in making activities to be more fun to do. Moreover, augmented reality technology also shows enormous potential in the world of education. This research developed a game-based historical learning application using augmented reality to enhance user experience in learning history. The application is built using the Unity Game Engine and Vuforia. Furthermore, the application was tested and evaluated by measuring the perceived usefulness and perceived ease of use following the guidance in the Technology Acceptance Model. The result shows that the application achieves 89.5% for perceived usefulness and 86.33% for perceived ease of use.